Gynaecological surgery in women over 70 - Borsuk, Anna; Skręt-Magierło, Joanna; Kluz, Tomasz; Skręt, Andrzej (Menopause Review/Przegląd Menopauzalny, 2008)
Objective: The aim of the study was to report clinical characteristics, risk factors for perioperative complications, types of surgery performed, and perioperative morbidity in women over 70 years old who underwent gynaecologic surgery. Material and methods: Among 326 women operated on in the Clinical Department of Obstetrics and Gynaecology in Rzeszów from May to August 2008 a group of 30 patients over 70 years old was selected. 8 of them were disqualified from surgery because of high risk. Results: In this group of patients the most common indications were endometrial, ovarian and vulvar cancer and pelvic organ prolapse. The most common coexisting general diseases were arterial hypertension, myocardial ischaemic disease, diabetes and varicosis. The usual preoperative time of hospitalization was 8 days and postoperative 5-6 days. In almost all patients the postoperative decrease of haemoglobin concentration was 1 g%. Conclusions: Advanced age of patients is a challenge to the gynaecological surgeon. The surgery and perioperative care must be individualized.